Piscicultura no Açude Castanhão em Jaguaribara Ceará: Uma Avaliação Econômica, Social e Ambiental - Silva Neta, Maria Enésia da (2016)
This thesis evaluates the effects of associative pens aquaculture activities in selected communities located in the municipality of Jaguaribara, into the Castanhão reservoir, and its capacity into promoting sustainable development for the involved communities into the Castanhão. To reach the objectives of this work, a case study was conducted upon pens aquaculture projects into the Castanhão reservoir, aiming at evaluating the effects of aquiculture activity and its capacity to promote sustainable development for the communities involved into the production. Hence the importance of researches based on mechanisms that result in a balance between economic, social and environmental aspects. The study uses primary data collected with the communities’ fishermen. We estimate economic and social well-being and also deprivation indicators of the families involved into the activities, seeking to understand if the current living pattern is different from the dominant pattern of the municipality of Jaguaribara. The study determinates the economic allocation of resources and evaluates the economic convenience of trimestral scaled production as well as if it is viable, on an economic point of view, to separate and sell viscus. This last subject has an important environmental impact, as it is highly pollutant, and is disposed inappropriately, it would contaminate either superficial reservoirs or underground aquifers. To study the scaled production optimization, we will minimize the production cost function, as we know the trimestral unitary costs. Selling prices of collected fishes were registered through interviews. This way, we generated minimum income restrictions, which was established in this study as at least one minimum wage by trimester. As for the viscus, we established a value equivalent to 10% of the living fish weight as a selling value. Costs considered are those regarding manpower need for viscus extraction. Results show that fishermen involved in this study have a much better standard of living than those observed in the municipality of Jaguaribara in 2010. The study also suggests that minimum production costs occur when production is distributed within the four analyzed trimesters, but with a higher concentration during the third trimester. Regarding the viscus extraction for separate sell, economic results were satisfactory and showed that a higher concentration of production, seeking minimizing costs, should occur during the second trimester. This study concludes that the project is economically viable, offers better living standards for the involved and has a strong environmental positive externality, as it uses viscus to produce biodiesel, saving oil and not contaminating the environment.